Necroptosis and autophagy in cisplatinum-triggered nephrotoxicity: Novel insights regarding their prognostic and diagnostic potential - Mai O. Kadry; Rehab M. Abdel-Megeed (Toxicology Reports)
Necroptosis is an innovative class of programmed autophagy (Atg) and necrosis; considered as a type of homeostatic housekeeping machinery that have observed an escalating concern due to its power in alleviating Cisplatinum-induced nephrotoxicity. This article elucidated in details the prospective role of both autophagy and necroptosis on Cisplatinum-triggered nephrotoxicity and investigating more potent therapy via lactoferrin and Ti-NPS conjugation. Cisplatinum is a commonly used chemotherapeutic drug; one of the limiting adverse actions of cisplatinum is renal toxicity. Upon cisplatinum administration, autophagy is highly stimulated in the kidney to shield against nephrotoxicity. Atg is a lysosomal degradation process which discards detorirated proteins to retain cell homeostasis. This article summarizes necroptosis progress in reconizing cisplatinum nephrotoxicity and debates how this progress can help in discovering more potent therapy via lactoferrin and Ti-NPS conjugation via monitoring autophagy and apoptotic biomarkers X-box-binding protein 1 (XBP), C/EBP homologous protein (CHOP), hypoxanthine phosphoribosyltransferase-1 (HPRT), FKBP prolyl isomerase 1B (FKBP), Cellular myelocytomatosis oncogene (C-myc), tumor suppressor gene (P53) and tumor necrosis factor (TNF-α). Cisplatinum nephrotoxicity was conducted in rat model via an oral dose of (2 mg/kg BW) for one month furthermore a comparative study was conducted among TiNPs-loaded Cisplatinum and Lactoferrin loaded Cisplatinum. Loaded drug delivery system counteracted Cisplatinum triggered nephrotoxicity via controlling autophagy and apoptotic XBP, CHOP, HPRT, FKBP, C-myc, P53 and TNF-α signaling pathway.